Analisis Kesalahan Penulisan Kanji Berdasarkan Hitsujun Pada Mahasiswa Angkatan 2021 Program Studi Pendidikan Bahasa Jepang FKIP Universitas Riau - Ayu Rinda Wangi; Nana Rahayu; Sri Wahyu Widiati (Journal on Education, 2024)
In Japanese language education, mastering kanji is one of the basic aspects that is very important because kanji are widely used in learning. However, there are still students who make mistakes when writing kanji by not writing them in the correct stroke order (hitsujun). The large number of kanji that must be learned, students who do not have a kanji culture background, and limited learning time in class are factors that cause students to have difficulty in remembering the correct hitsujun kanji. This study aims to find out and describe kanji writing errors based on hitsujun in 2021 students of Japanese Language Education Study Program FKIP Riau University. The method used in this research is descriptive qualitative. The data was taken from a kanji writing test given to the research sample and then analyzed the errors in writing hitsujun kanji based on the principles of writing kanji sequences. The result of this study is the error rate of kanji writing that is not in accordance with the correct hitsujun of 56.96%. The writing errors are grouped based on the principles of kanji sequence writing. In addition, five other groups of writing errors were also found.